Digital Astrophotography: The State of the Art - Ratledge, David (The Patrick Moore Practical Astronomy Series,, 2005)
Patrick Moore's Practical Astronomy Series DIGITAL ASTROPHOTOGRAPHY The State of the Art This book is the successor to David Ratledge's much-acclaimed The Art and Science of CCD Astronomy. CCD cameras and their associated technologies have continued to make great strides since the original book was first published almost eight years ago, particularly in the universal availability of color cameras and in the dramatically lower cost of equipment. Digital Astrophotography: The State of the Art provides examples of the latest and best images, and describes how to get the best out of this extraordinary technology. Experts in CCD astronomy from North America and Europe have contributed, illustrating their help and advice with many beautiful color images. The techniques explained here range from the use of inexpensive webcams, through to highly technical aspects such as supernovae patrolling. Computer processing, stacking and image-enhancement are also detailed, along with many hints and tips from the experts.